Size-dependent pattern of wilfire ignitions in Portugal: when do ignitions turn into big fires ? - Moreira, Francisco (2012)
Not all wildfire ignitions result in burned areas of a similar size. The aim of this study was to explore whether there was a size-dependent pattern (in terms of resulting burned area) of fire ignitions in Portugal. For that purpose we characterised 71,618 fire ignitions occurring in the country in the period 2001–2003, in terms of population density in the local parish, land cover type and distance to roads. We then assigned each ignition into subsets of five classes according to the resulting burned area:[5 ha, [50 ha,[100 ha,[250 ha,[500 ha. The probability of an ignition resulting in different burned area classes was modelled using binary logistic regression, and the relative importance, strength and signal (positive or negative) of the three explanatory variables compared across the models obtained for the different classes. Finally, we explored the implications of land cover and population density changes during the period 1990–2000 in Portugal for the likelihood of ignitions resulting in wildfires[500 ha. Population density was the more important variable explaining the resulting burned area, with the probability of an ignition resulting in a large burned area being inversely related to population density. In terms of land cover, ignitions resulting in large burned areas were more likely to occur in shrubland and forest areas. Finally, ignitions farther away from roads were more likely to result in large burns. The current land cover trends (decrease of agricultural land and increase in shrublands) and population trends (decline in population densities except near the coast) are increasing the probability that ignitions will result in large fires in vast regions of the country.